The rare subgroup C1 of Marphysa (Polychaeta, Eunicidae): re-description of species and first records in the Mediterranean Sea - Katsiaras, Nikolaos; Simboura, Nomiki; Koutsoubas, Drosos (Zootaxa, 2014)
Marphysa is one of the largest genera in the family Eunicidae, containing 76 valid species. However, among them there are only five species that share the diagnostic characters of having only composite falcigers in inferior setae and branchiae confined in the anterior body. These species are relatively rare and less described while in their original descriptions their differentiation is mainly based on features believed to be age-specific today. In this study, the type-materials of M. adenensis, M. purcellana and M. gemmata have been re-examined and re-described with illustrations. For M. adenensis, new material from the Mediterranean Sea was also examined, where this group has not been recorded up to date. The above species were compared to each other and new differential characters are being highlighted. A revised key for the Marphysa species found in the Mediterranean is also provided.
World Polychaeta Database (WPolyDb)